Ewolucja filozoficznego rozumienia pojęcia kultury - Koropczuk, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Nothing is vaguer than the word culture and nothing more misleading when culture is used to describe nations and eras. J.G. HerderThis article is an attempt to present the basic and most significant conceptions of understanding culture. It focuses around the evolution of different ways to interpret culture and what basic elements it consists of. Although we use the word “culture” rather often, each of us understands this notion differently. In this paper we can find the basic view on culture “as is” and how the concept of culture is assimilated by the theory of law. The perspective of culture is used to build such expressions as culture of rights, cultural defense.In attempts to resolve multicultural problems or different moral cultures we have to able to discuss culture. We must better understand its perception and reflect on how it can be interpreted.
Keywords: kultura; kultura prawna; nośnik kultury; zakres kultury; wielokulturowość